Pelaksanaan Layanan Bimbingan Kelompok untuk Menyiapkan Mental Siswa Menghadapi Ujian Nasional - Olfakhrina, Olfakhrina; Syahniar, Syahniar; Nirwana, Herman (Universitas Negeri Padang, 2014)
The implementation of Group Guidance Services to Prepare The Mental of The Students in Facing National Examination. This study generarally aims to examine the effectiveness of group guidance services in increasing student’s mental readiness in facing the National Examination. Two groups were selected by using selected purposive sampling these groups will be used as the experimental group and the control group. Each group consisted of 8 students. The research finding shows that there are difference of student’s mental readiness in facing the National Examination before and after participating in group guidance activities. In general there is group guidance services effective in increasing student’s mental readiness in facing the National Examination